Issues Facing Pharmacy Leaders in 2015: Suggestions for Pharmacy Strategic Planning - Weber, Robert J. (Hosp Pharm, 2015)
Issues facing pharmacy leaders in 2015 include practice model growth and the role of pharmacy students, clinical privileging of health-system pharmacists and provider status, medication error prevention, and specialty pharmacy services. The goal of this article is to provide practical approaches to 4 issues facing pharmacy leaders in 2015 to help them focus their department’s goals. This article will address (1) advances in the pharmacy practice model initiative and the role of pharmacy students, (2) the current thinking of pharmacists being granted clinical privileges in health systems, (3) updates on preventing harmful medication errors, and (4) the growth of specialty pharmacy services. The sample template of a strategic plan may be used by a pharmacy department in 2015 in an effort to continue developing patient-centered pharmacy services.